Different dissecting orders of the pulmonary bronchus and vessels during right upper lobectomy are associated with surgical feasibility and postoperative recovery for lung cancer patients. Issue 1 (27th June 2017) - Zhai, Hao‐Ran; Yang, Xue‐Ning; Nie, Qiang; Liao, Ri‐Qiang; Dong, Song; Li, Wei; Jiang, Ben‐Yuan; Yang, Jin‐Ji; Zhou, Qing; Tu, Hai‐Yan; Zhang, Xu‐Chao; Wu, Yi‐Long; et al.
Abstract: Background: Right upper lobectomy (RUL) for lung cancer with different dissecting orders involves the most variable anatomical structures, but no studies have analyzed its effects on postoperative recovery. This study compared the conventional surgical approach, VAB (dissecting pulmonary vessels first, followed by the bronchus), and the alternative surgical approach, aBVA (dissecting the posterior ascending arterial branch first, followed by the bronchus and vessels) on improving surgical feasibility and postoperative recovery for lung cancer patients. Methods: According to the surgical approach, consecutive lung cancer patients undergoing RUL were grouped into aBVA and VAB cohorts. Their clinical, pathologic, and perioperative characteristics were collected to compare perioperative outcomes. Results: Three hundred one patients were selected (109 in the aBVA cohort and 192 in the VAB cohort). The mean operation time was shorter in the aBVA cohort than in the VAB cohort (164 vs. 221 min, P < 0.001), and less blood loss occurred in the aBVA cohort (92 vs. 141 mL, P < 0.001). The rate of conversion to thoracotomy was lower in the aBVA cohort than in the VAB cohort (0% vs. 11.5%, P < 0.001). The mean duration of postoperative chest drainage was shorter in the aBVA cohort than in the VAB cohort (3.6 vs. 4.5 days, P = 0.001). The rates of postoperative complications were comparable ( P = 0.629). The median overall survival was not arrived in both cohorts ( P > 0.05). The median disease‐free survival was comparable for all patients in the two cohorts (not arrived vs. 41.97 months) and for patients with disease recurrences (13.25 vs. 9.44 months) (both P > 0.05). The recurrence models in two cohorts were also comparable for patients with local recurrences (6.4% vs. 7.8%), distant metastases (10.1% vs. 8.3%), and both (1.8% vs. 1.6%) (all P > 0.05). Conclusions: Dissecting the right upper bronchus before turning over the lobe repeatedly and dissecting veins via the aBVA approach during RUL would promote surgical feasibility and achieve comparable postoperative recovery for lung cancer patients.